Poly(ethylene glycol)‐based poly(urethane isocyanurate) hydrogels for contact lens applications. Issue 2 (26th November 2019) - Driest, Piet J; Allijn, Iris E; Dijkstra, Dick J; Stamatialis, Dimitrios; Grijpma, Dirk W
Abstract: Over the past few decades, the global use and market of contact lenses have expanded steadily. Due to the many demands on material properties (e.g. mechanical, optical and biological), the development of novel contact lens materials is challenging. Specifically, the ideal combination of high equilibrium water content, high toughness in the hydrated state and low protein adsorption is difficult to realize. In this work, poly(ethylene glycol)‐based poly(urethane isocyanurate) (PEG PUI) type hydrogels that combine the above important properties are presented as a new class of materials for contact lens applications. It is shown that these PEG PUI hydrogels demonstrate high toughness values in the hydrated state ranging from 98 to 226 kJ m −3 and elastic moduli ranging from 0.8 to 17.2 MPa for networks with equilibrium water contents ranging from 76.3 to 16.1 wt%. These hydrogels also demonstrate transmittance values >90% across the visible spectrum, clarities close to 100% in most cases and refractive indices ranging from 1.48 to 1.36. Importantly, these hydrogels are non‐cytotoxic and demonstrate lower bovine serum albumin adsorption values than several commercial contact lenses of 0.24 to 0.65 mg g −1 compared to 0.55 to 1.38 mg g −1 after 24 h, respectively. This combination of high equilibrium water content, high toughness in the hydrated state and low protein adsorption is exceptional. These properties can be attributed to the PEG PUI network structure: the use of a PEG polymeric backbone provides hydrophilicity and chemical inertness while the PUI‐type crosslinking units provide high toughness in the hydrated state. © 2019 The Authors. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Poly(urethane isocyanurate)‐type hydrogels, synthesized by the trimerization of NCO‐functionalized poly(ethylene glycol) prepolymers, are presented as a promising new class of materials for contact lens applications.